Borotellurite bio-silica glasses doped by erbium nanoparticles: structural and thermal properties - Muhammad Hamza, Abdulkarim; Aliyu, Umar Sa’ad; Mohamed Kamari, Halimah; Geidam, Ibrahim Gana; El-Mallawany, Raouf; Nazrin, Nazrin; Baba, Muhammad Nasirudeen (Springer, 2022)
[(TeO2)0.8 (B2O3)0.2]0.8 (SiO2)0.2}0.99 (Ag2O)0.01]1-y - (Er2O3 NPs)y, and y=0.01,0.02,0.03,0.04 and 0.05 mole% were fabricated by the melt quenching technique. X-ray diffraction (XRD) was used to verify and confirm the glasses’ non-crystallinity. X-ray fluorescence (XRF) proved the achievement of silicate of 98.6% quality from rice husk. Fourier transform infrared d (FTIR) results exposed the basic structural units such as TeO4, TeO3, BO4, BO3, Si-O-Si, and O-Si-O within the network. The concentration of Er2O3 nanoparticles’ effects on the thermal properties of ErDBST glasses was duly discussed. From the profiling of the differential scanning calorimetry (DSC), the glass crystallization temperature Tc, and transition temperature Tg are estimated. Also, the thermal stability factor, defined as Ts = Tc - Tg, was higher than 100 oC. From room temperature above the Tg for all the sample glasses, specific heat capacity Cq (≥1.4 J/gK-1) was obtained. The results showed that the glass thermal stability and the transition temperature increase with the addition of Er2O3 nanoparticles (NPs). These suggest that an ErDBST glass exhibit good thermal stability and consequently is a suitable candidate for fiber drawing.